Structural elucidation of thermostable L2 lipase based on ground and microgravity grown crystals - Mohd Shariff, Fairolniza (2012)
The number of lipases that have been studied has grown tremendously over the last decades. The motivation to use X-ray crystallography as the primary means of structure determination structures lies mainly in the fact that accurate and precise molecular structures, sometimes at near atomic resolution, can be obtained rapidly and reliably via X-ray crystallography. The ultimate goal of protein expression and purification is to obtain a single crystal that diffracts well in structural determination through X-ray diffraction analysis. The amount of protein with high purity (~99 %) is the crucial step prior to protein crystallization. Thus, good protein purification strategies for L2 lipase were designed in order to get high yield of highly purified L2 lipase that can be used for crystallization experiments. The recombinant thermostable L2 lipase which was expressed in Escherichia coli system was purified to 1.6-fold with 76.1% yield and a specific activity of 45.5 U/mg by using affinity chromatography. The enzyme was detected to have a molecular weight of 43 kDa. The optimum pH and temperature were 9.0 and 70ºC, respectively. The enzyme was stable in the pH range of 9.0 to 10.0 for 30 min where the residual activity was retained up to more than 50%. The metal ions Ca2+ strongly activated the lipase activity by 100% and 200% when treated with the concentrations 1mM and 5 mM, respectively. Presence of K+, Na+ and Mn2+ also increased the lipase activity by more than 100%. Lipase L2 was strongly inhibited by EDTA (100%), while PMSF, pepstatin A, 2-mercaptoethanol and DTT showed more than 40% of inhibitions. 3-D structure of L2 lipase was predicted using homology modelling method. The predicted structure was evaluated with Ramachandran plot and Errat. The Ramachandran plot of predicted L2 lipase structure showed that 88.8 % (293) of residues lie in the most-favoured region, with 10.6 % (35) of residues in the additional allowed region. As the structure was derived from a 1.8 Å resolution of crystal structure of T1 lipase (2dsnA), the confidence level of 7.35% significantly well-determined the correctness of the predicted structure of L2 lipase when it was analysed using Errat program. Based on the evaluations, the predicted structure was in high similarity with its template; crystal structure of T1 lipase (2DSN), thus can be accepted and used in further studies. Crystallization of L2 lipase was done using both vapour diffusion and counter diffusion methods with various different commercial crystallization screens as well as modified formulations. Formulation consisted of 20% PEG 6000, 50 mM MES pH 6.5 and 50 mM NaCl was found to be the best formulation to produce crystals with good shape and size. The approximate dimensions of the crystal are 0.25 X 0.2 X 0.05 mm. The protein concentration used for the crystallization was 3 mg/mL. When using vapour diffusion method, the crystals were formed after 24 h incubation at 20°C, while for counter diffusion method, the incubation period was 10 days. It was found that ground-grown L2 lipase crystal has two forms of crystals; Shape 1 and Shape 2. Preliminary X-ray data processing of ground-grown L2 lipase crystals Shape 1 produced by counter diffusion method showed that the crystal was successfully diffracted at 2.7Å with good processing statistics. The crystals belong to theorthorhombic space group P212121, with unit-cell parameters a = 87.4, b = 94.9, c = 126.5 A ˚, α=β=γ=90°. There are two molecules per asymmetric unit and the solvent content of the crystals is 57.0%, with a Matthew’s coefficient of 3.05 Å3 Da-1. Crystallization of L2 lipase under microgravity condition experiment utilized counter diffusion method. Structural determination and comparison of microgravity and ground grown protein crystals have been carried out in order to investigate the effect of microgravity on the structure of protein crystals. The Ground Unit for microgravity experiment produced both Shape1 and Shape 2 L2 lipase crystals. However, the results obtained from the Space Unit showed that under microgravity condition, only Shape 1 crystal form of L2 lipase was able to grow. X-ray diffraction of L2 lipase Shape 1 Space crystal gave better diffraction data as (diffracted at 2.3 Å) compared to the crystals of the L2 lipase Shape 1 produced by the Ground Unit. When diffracted, the crystals of L2 lipase Shape 1 produced by the Ground Unit ave low resolution data (more than 3 Å) with bad mosaicity range thus, the data could not be processed. The Space-grown Shape 1 L2 lipase crystals belong to the orthorhombic space group P212121, with unit-cell parameters a = 87.8, b = 95.1, c = 126.1 A˚, α=β=γ=90°. There are two molecules per asymmetric unit and the solvent content of the crystals is 59.3%, with a Matthew’s coefficient of 3.12Å3 Da-1. Among all crystals that have been diffracted in this study, based from the structural data analysis, the Ground-grown Shape 2 L2 lipase crystal obtained from the Ground Unit produced highest resolution crystal structure (1.5 Å). The high resolution structure of Shape 2 Ground L2 lipase crystal belong to the orthorhombic space group P212121, with unit-cell parameters a = 72.0, b = 81.8, c = 83.4 A˚, α=β=γ=90°. There is one molecule per asymmetric unit and the solvent content of the crystals is 56.9%, with a Matthew’s coefficient of 2.85 A˚3 Da-1. Both crystal structures of L2 lipase Shape 2 Ground and L2 lipase Shape 1 Space were refined and the final models were evaluated. For the structure of Ground-grown L2 lipase Shape 2 of Ground Unit, the final Rfactor obtained was 0.167 with Rfree value of 0.189, with a B-factor value of 15.01. For L2 lipase Shape 1 Space of the Space Unit, the final refined structure was achieved with Rfactor value of 0.227 and Rfree value of 0.279 with B-factor value of 21.66. Based on the refinement statistic results, the L2 lipase Shape 2 crystal produced a better crystal structure as compared to L2 lipase Shape 1 crystal. The 3D structure of L2 lipase revealed topological organization of α/β-hydrolase fold consisted of 11 β-strands and 13 α-helices. Ser-113, His-358 and Asp-317 were assigned as catalytic triad residues. One Ca2+ and one Zn2+ were found in each of the molecules of L2 lipase. Both of the L2 lipase crystal structures were sent for evaluation. They were evaluated with Ramachandran plot, Verify 3D and Errat programs. The Ramachandran plot evaluation showed that 91.1% of the residues in the crystal structure of L2 lipase Shape 2 Ground crystal lie in most favoured region, while 87.5% of residues for the crystal structure of L2 lipase Shape 1 Space crystal lie in this same region. Evaluations of the crystal structures by using Errat and Verify 3-D showed that both crystal structures gave values that were in the acceptable range of good protein structures. From this study, it can be concluded that there was a polymorphism in L2 lipase crystals that resulted in production of two different shapes of protein crystals; Shape 1 and Shape 2. Shape 1 crystal can be produced both on Ground and in microgravity conditions, while Shape 2 crystal can only be produced on Ground. Microgravity improved the quality of L2 lipase Shape 1crystals where it was found that for the microgravity experiment, only Spacegrown Shape 1 crystal can be diffracted and produced good diffraction data while its Ground-grown control Unit was not able to produce useful diffraction data. However, the best 3-D crystal structure was obtained by L2 lipase Shape 2 crystal with highest resolution as compared to crystal structures of L2 lipase Shape 1 crystals.